RELEVANSI NILAI INFORMASI AKUNTANSI, SEBELUM ADOPSI IFRS DAN SETELAH ADOPSI IFRS PADA PERUSAHAAN YANG TERCATAT DALAM BURSA EFEK INDONESIA - Kusumo, Yuro Bimo; Subekti, Imam (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aimed to explore the value relevance of accounting information in the period before and after the adoption of IFRS in Indonesia . This study uses the value of accounting earnings and book value of equity as a proxy for the value relevance of accounting information . Quality of accounting information can be seen on the relevance of accounting information in the decision-making of investors as reflected in the stock price . Adoption of IFRSÂ  -based standards are not predicted to improve the quality of accounting information due toÂ  spesific environmental factors in Indonesia . The population of this research is a listed public company on the Indonesia Stock Exchange in the period 2009-2012 . The results showed that the adoption of IFRS -based standards in Indonesia have not been able to improve the quality of accounting information . this is due to only the relevance of equity book value are increased , while the relevance of accounting earnings with investment decisions as reflected in the stock price does not increase significantly in the period after the adoption of IFRS. Keyword: Value relevance, Accounting Earnings, Book Value of Equity, IFRS adoption.